Analysis of Factors Affecting The Body Temperature of Postoperative Patients At RSUP Dr. M Djamil Padang - Neurosurgeon, Jefri Henky, MD.,; Rhamadani Adma, Enno (Jurnal Health Sains, 2024)
Introduction: Surgery is a medical procedure carried out using invasive methods by opening, cutting or slashing parts of the body to provide treatment to the patient. Changes in body temperature can occur in post-operative patients which are influenced by age, gender, body mass index (BMI), duration of surgery, and type of surgery. Objective: To analyze the factors that influence the body temperature of post-operative patients at RSUP Dr. M. Djamil Padang. Methods: This study is a correlative analytical research using cross sectional design. This study was conducted using primary data and the samples were selected by consecutive sampling technique with a total of 56 samples. Results:  The results of this study show that there is a relationship between age with body temperature of the patients after surgery (p=0,021, r=-0,308), there is no relationship between gender with body temperature of the patients after surgery (p=0,876, r=0,021), there is a relationship between BMI with body temperature of the patients after surgery   (p=0,033,  r=0,140), there is a relationship between duration of surgery with body temperature of the patients after surgery (p=0,027, r=-0,482), and there is no relationship between type of surgery with body temperature of the patients after surgery (p=0,762, r=0,041).  Conclusion:  There is a significant relationship between age, BMI and duration of surgery with body temperature of the patient's after surgery and there was no significant relationship between gender and type of surgery with body temperature of the patient's after surgery.